Alterations in ganglion cell and nerve fiber layer in Leber hereditary optic neuropathy across clinical stages - Michael Oeverhaus; Mareile Knetsch; Ying Chen; Leyla Jabbarli; Carmen Nolden; Anja Eckstein; Nikolaos E. Bechrakis; Philipp Rating (BMC Ophthalmology)
Abstract Purpose LHON leads to gradual, painless, and permanent vision loss in both eyes, often associated with central scotomas. As the condition progresses, there is a decline in visual function, accompanied by noticeable structural alterations. This study focused on evaluating the clinical characteristics of patients with differing LHON stages, with a specific emphasis on optical coherence tomography (OCT) imaging results. Methods This analysis included 22 individuals with LHON. Patients underwent thorough clinical ophthalmologic assessments, including SD-OCT, Visual evoked potentials, and perimetry. When LHON was suspected, blood samples were obtained to test for the three major mitochondrial mutations (G1178A, T14484C, G3460A), with further sequencing to identify additional known mutations. The data were subsequently examined through descriptive statistical methods. Results The clinical characteristics of 22 individuals (median age 33, range 9–68) were examined. All participants carried a mutation linked to LHON. The most prevalent mutation was G11778A (55%), followed by G3460A (23%), T14484C (14%), with one instance each of the rare G13042A and C3461T mutations. Fourteen participants experienced acute vision loss (average duration: 5.2 ± 5 months), while eight had chronic LHON. There was no significant difference in visual acuity (VA, logMAR) between the two groups (0.9 vs. 0.9, p = 0.91). However, chronic patients exhibited significantly reduced the retinal nerve fiber layer (RNFL), especially in the temporal region (32 μm vs. 56 μm, p < 0.0001), but not in the nasal region. Ganglion cell layer (GCL) thickness was also notably thinner in the temporal area for chronic patients compared to those with acute LHON (22 μm vs. 28 μm, p = 0.04). Linear regression analysis showed correlations between RNFL and GCL and visual acuity (R² = 0.18, p = 0.007 and R² = 0.1, p = 0.05). Conclusion In our analysis, we observed an unusual pattern in the genetic mutations, with G3460A being the second most frequent, rather than T14484C, which may be attributed to the limited sample size. 14 patients experienced acute or subacute vision loss, while eight were assessed for chronic disease. Those with chronic LHON demonstrated significantly thinner GCL and RNFL. These results underscore the importance of accelerating both diagnosis and treatment to facilitate prompt intervention for patients.